Percutaneous left atrial appendage closure: current state of the art. (January 2017) - Jazayeri, Mohammad-Ali; Vuddanda, Venkat; Parikh, Valay; Lakkireddy, Dhanunjaya R.
Abstract : Purpose of review: The authors reviewed the seminal and more recent literature surrounding the major modalities for percutaneous left atrial appendage closure used in contemporary practice, with particular emphasis on safety and efficacy, technical challenges, and future developments. Recent findings: Along with the continued practice of surgical left atrial appendage closure, which has evolved substantially with the advent of clipping techniques, a number of percutaneous methods have been developed to close the left atrial appendage with endocardial, epicardial, and hybrid approaches. The last 18 months has seen the Food and Drug Administration approval of the WATCHMAN device for stroke prevention in the United States, the initiation of a randomized controlled trial to further examine the LARIAT device, and an increasing body of literature surrounding use of the AMPLATZER Amulet in Europe. Summary: Left atrial appendage closure is a promising alternative to systemic anticoagulation for stroke prevention in appropriate atrial fibrillation patients. The wealth of available data for the various modalities sheds light on the strengths and limitations of each, postprocedural complications and their management, and new areas for exploration. With a plethora of new devices on the horizon, it is a very exciting time in the field of 'appendage-ology' as we pursue new avenues to optimize care for atrial fibrillation patients.